Analisis Kepuasan Pelanggan dalam Meningkatkan Kinerja Mutu Atribut Produk Mainan Edukatif (Studi Kasus: Produk ’Shofia Toys’) - Yulita Veranda Usman; Budi Suharjo; Darwin Kadarisman (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2010)
Children love to play and want to know about anything in their surrounding.  They need to grow and educational toys can facilitate them. The aim of this study was to improve quality performance of product attributes of Shofia Toys by analyzing its customer satisfaction. Data analysis methods that used in this study were: focus group discussion (FGD) to identify educational toy attributes; top two boxes index to measure customer satisfaction level; and gap analysis, penalty-reward analysis and diagonal analysis to analyze influential factors of customers satisfaction.  CHAID analysis was used to determine which one of the product attributes to be the priority of improvement. There are 26 educational toy attributes that can be grouped into 6 quality dimensions of product, they are performance, reliability, aesthetics, conformance, durability, and serviceability.  Customer satisfaction level of Shofia Toys products is 62,5% and dissatisfaction level is 1,0%.  Based on the hierarchy of needs, all attributes are performance attributes, but their performance are not sufficient yet and have 19-47% of gaps between important and satisfaction level.  At this time, company can do an improvement for the attibutes that related to ability to increase creativity of children; precision; durability; and smoothness of wood product.  These are the priorities of quality performance improvement of Shofia Toys product attributes that can improve its customer satisfaction